2002
DOI: 10.1073/pnas.252339399
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of cell migration in the fish lateral line: Role of the chemokine receptor CXCR4 and of its ligand, SDF1

Abstract: Cell migration plays an essential role in many morphogenetic processes, and its deregulation has many dramatic consequences. Yet how migration is controlled during normal development is still a largely unresolved question. We examined this process in the case of the posterior lateral line (PLL), a mechanosensory system present in fish and amphibians. In zebrafish, the embryonic PLL comprises seven to eight sense organs (neuromasts) aligned from head to tail along the flank of the animal and is formed by a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
262
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(284 citation statements)
references
References 22 publications
15
262
0
4
Order By: Relevance
“…Finally, we observed that the sox3-expressing p4 subdomain migrates posteriorly from its original domain along the body axis after the 20-somite stage (data not shown). Given that this migration trend of the p4 subdomain is similar to that of the posterior lateral line primordium, as revealed by morphological observation (Laguerre et al, 2005) and expression of the chemokine receptor cxcr4 (Chong et al, 2001;David et al, 2002), we suggest that the p4 subdomain represents the anlage of the posterior lateral line system.…”
Section: Early Development Of the Epibranchial Placode In Zebrafishsupporting
confidence: 54%
“…Finally, we observed that the sox3-expressing p4 subdomain migrates posteriorly from its original domain along the body axis after the 20-somite stage (data not shown). Given that this migration trend of the p4 subdomain is similar to that of the posterior lateral line primordium, as revealed by morphological observation (Laguerre et al, 2005) and expression of the chemokine receptor cxcr4 (Chong et al, 2001;David et al, 2002), we suggest that the p4 subdomain represents the anlage of the posterior lateral line system.…”
Section: Early Development Of the Epibranchial Placode In Zebrafishsupporting
confidence: 54%
“…It has been shown that migration of the posterior lateral line primordium depends on the interaction between CXCR4 (chemokine receptor) and its ligand SDF1 (stromal-derived factor). While the migrating cells express CXCR4, its ligand SDF1 is found in the horizontal myoseptum (David et al, 2002). The same mechanism is reported in mouse germ cell migration and survival (Molyneaux et al, 2003).…”
Section: Introductionsupporting
confidence: 58%
“…The embryonic PLL is generated by a sensory primordium, which migrates along a defined pathway, from the head to the tip of the tail (Harrison, 1904;Stone, 1937;Metcalfe, 1985). In zebrafish, primordium migration depends on SDF1 signaling by cells along the path of migration (David et al, 2002;Li et al, 2004;Haas and Gilmour, 2006; reviewed in Ghysen and Dambly-Chaudière, 2007). The direction of migration depends on the anisotropic distribution of two SDF1 receptors, CXCR4 which is present in the leading two-thirds of the primordium, and CXCR7 which is present in the trailing third Valentin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the binding of SDF1 to CXCR4 drives the migration (David et al, 2002), CXCR7 acts as an atypical receptor (Comerford et al, 2007) that may sequester SDF1 (Balabanian et al, 2005) in the trailing region of the primordium and thereby provide directionality to the migration . Alternatively or additionally, CXCR7 may contribute to migration independently of CXCR4 (Valentin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%